2019
DOI: 10.1002/fsn3.876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold plasma on essential oil content and composition of lemon verbena

Abstract: Cold plasma is known as a novel nonthermal processing method for decontamination of medicinal and aromatic plants ( MAP s); however, there are little research studies about its effects on active ingredients of these plants. The aim of this research was to investigate the influence of low‐pressure cold plasma ( LPCP ) treatments (1, 3, and 5 min) on the essential oil (EO) content and composition of lemon verbena leaves. The EO content was determined using hydro‐dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 31 publications
5
28
0
Order By: Relevance
“…Thus, it can be concluded that the intensity of the odor of the extracts after plasma treatment decreased. The same effect of plasma on the reduction of the volatile compound profile was observed for lemon verbena leaves treated with plasma for 5 min [ 30 ]. Plasma treatment may disintegrate the cellular structures in the same manner as in the case of microbes [ 6 ].…”
Section: Resultsmentioning
confidence: 61%
“…Thus, it can be concluded that the intensity of the odor of the extracts after plasma treatment decreased. The same effect of plasma on the reduction of the volatile compound profile was observed for lemon verbena leaves treated with plasma for 5 min [ 30 ]. Plasma treatment may disintegrate the cellular structures in the same manner as in the case of microbes [ 6 ].…”
Section: Resultsmentioning
confidence: 61%
“…Plasma sources can be delivered to the object either directly (sample comes into direct connection with the plasma area) or indirectly (sample contacts the plasma or plasma-activated media) [ 60 ]. Cold plasma has been investigated for enhancement of the drying efficiency and quality of different foods, medicinal plants, and herbs, such as shiitake mushrooms [ 58 ], chili peppers [ 61 ], corn kernels [ 62 ], wolfberries [ 63 ], jujube slices [ 64 ], saffron [ 65 ], grapes [ 66 ], lemon verbena [ 67 ], coneflower leaves [ 68 ], and many others. All of these authors remarked that CP pre-treatment can significantly increase the drying efficiency and product quality concerning phytochemicals or microbial safety.…”
Section: Postharvest Operations Involved In Cannabismentioning
confidence: 99%
“…Various reactive oxygen and nitrogen species, along with free radicals, are produced by plasma depending on the gas used (Aparajhitha & Mahendran, 2019). They are widely used for surface treatment, and few studies have been reported in the field of essential oil extraction and oil composition analysis (Ebadi, Abbasi, Harouni, & Sefidkon, 2019; Kodama, Thawatchaipracha, & Sekiguchi, 2014; Pragna et al, 2019). Hence, in the current study, atmospheric pressure cold plasma gas has been bubbled through the mixture (solid–liquid phase) of cumin sample and distilled water in a 1:7 ratio at different input voltage and treatment time to analyze the cumin essential oil yield and changes in cuminaldehyde concentration.…”
Section: Introductionmentioning
confidence: 99%